Are Local Minimum Wages Absorbed by Price Increases? Estimates from Internet-Based Restaurant Menus. (January 2018) - Allegretto, Sylvia; Reich, Michael
The authors analyze 884 Internet-based restaurant menus from inside and outside San Jose, California, which they collected before and after the city implemented a 25% minimum wage increase in 2013. Their findings suggest that nearly all of the cost increase was passed through to consumers, as prices rose 1.45% on average. Minimum wage price elasticities averaged 0.058 for all restaurants and ranged from 0.044 to 0.109, depending on the type of restaurant. The authors' estimate of payroll cost increases net of turnover savings is consistent with these findings. Equally important, border effects for restaurants are smaller than is often conjectured. Price differences among restaurants that are one-half mile from either side of the policy border are not competed away, indicating that restaurant demand is spatially inelastic. These results imply that citywide minimum wage policies need not result in substantive negative employment effects nor shifts of economic activity to nearby areas.